(untitled) (Książnica Śląska, 2025)
The article describes the establishment and operation of one of the most important Polish scientific institutions founded in Upper Silesia in the interwar period – the Pedagogical Institute in Katowice. The paper presents the most critical goals, tasks and organization of the Institute, which solemnly inaugurated its activity on October 28, 1928. The most important periodical of the Institute – the pedagogical magazine “Chowanna” has been described in detail. “Cho-wanna” was published from 1929 to 1939. It was a scientific journal for the first two years, theoretically developing pedagogical, psychological, sociological and cultural issues. Later on, it functioned as a supporter and advocate of Polish educational culture and brought readers closer to the activity of the Pedagogical Institute in Katowice. Since 1935, the regional supplement “Sprawy Szkolne na Śląsku” (School Affairs in Silesia) was attached to the magazine.